1974
DOI: 10.1159/000467770
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Reproducibility of the Bromelised Test Cell Anti-D Assay Using the Auto-Analyser

Abstract: With the bromelised test cell technique, as commonly used, that is the autoanalyser manifold subject to ambient temperature with the exception of the incubation coils at 37 °C, an anomalous inherent variability has been observed in the anti-D assay of a certain proportion of antisera; these show a significant difference in the estimates of anti-D concentration obtained using the added bromelin and bromelised test cell techniques. The inherent error of assay exhibited by such antisera is partially dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…In this analysis, the five states of the disease were used as five populations and each technique of measuring the anti-D level was used Generally, an accuracy of between f10 and +20% has been achieved. However, like Moore and Hughes-Jones [ll] and Gunson et al [5], we found reproducibility to be dependent upon the serum in use. Some sera consistently had an accuracy as high as f 8% whilst others were as low as 2 35%.…”
Section: Analysis Of Resultssupporting
confidence: 79%
“…In this analysis, the five states of the disease were used as five populations and each technique of measuring the anti-D level was used Generally, an accuracy of between f10 and +20% has been achieved. However, like Moore and Hughes-Jones [ll] and Gunson et al [5], we found reproducibility to be dependent upon the serum in use. Some sera consistently had an accuracy as high as f 8% whilst others were as low as 2 35%.…”
Section: Analysis Of Resultssupporting
confidence: 79%
“…However, like Moore and Hughes-Jones [11] and Gunson et al [5], we found reproducibility to log2 titre was used in these analyses and loge micrograms for the microgram readings. The first step in the analysis was to con sider how well each of the three techniques for measuring anti-D levels related to the fetal outcome as measured by the fetal index.…”
Section: Accuracy Of the Autoanalyzer And Other Observationssupporting
confidence: 65%
“…Temperature has an important role when measuring low-affinity anti-D antibodies. Following the addition of rouleaux dispersal agent to the AutoAnalyser, there is an increase in the dissociation rate of antibody (Gunson et al, 1976). For low-affinity antibody, any increase in temperature from 12.5"C up to 37°C augments this effect.…”
Section: Discussionmentioning
confidence: 99%